2016
DOI: 10.1001/jamapsychiatry.2015.3097
|View full text |Cite
|
Sign up to set email alerts
|

Indicators for Remission of Suicidal Ideation Following Magnetic Seizure Therapy in Patients With Treatment-Resistant Depression

Abstract: IMPORTANCE Magnetic seizure therapy (MST) is a novel therapeutic option for treatment-resistant depression (TRD). Suicidal ideation is often associated with TRD and contributes to the increased mortality and morbidity of the disorder. OBJECTIVE To identify a biomarker that may serve as an indicator of remission of suicidal ideation following a course of MST by using cortical inhibition measures from interleaved transcranial magnetic stimulation and electroencephalography (TMS-EEG). DESIGN, SETTING, AND PARTICI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
107
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 113 publications
(112 citation statements)
references
References 64 publications
(29 reference statements)
4
107
0
1
Order By: Relevance
“…Focal stimulation of other regions, such as the dorsal frontal cortex, as recently reported in an open label sample (Sun et al, 2016), may produce better responses. However, systematic research is required to identify the optimal MST treatment target prior to the conduct of further comparative studies of the sort reported in this paper.…”
Section: Discussionmentioning
confidence: 54%
“…Focal stimulation of other regions, such as the dorsal frontal cortex, as recently reported in an open label sample (Sun et al, 2016), may produce better responses. However, systematic research is required to identify the optimal MST treatment target prior to the conduct of further comparative studies of the sort reported in this paper.…”
Section: Discussionmentioning
confidence: 54%
“…Such studies have demonstrated EEG neurophysiological correlates of cortical inhibitory circuits such as GABA B -mediated longinterval intracortical inhibition (LICI) in motor and dorsolateral prefrontal cortex (DLPFC) Fitzgerald et al, 2008). Changes in this paradigm have been associated with schizophrenia Radhu et al, 2015) and predict treatment response to magnetic seizure therapy in depression (Sun et al, 2016). Changes are typically characterized by modulation in the amplitude of components of the TMS-evoked potential (TEP) and modulation of oscillatory power at different frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…Маркеры ТМС-ЭЭГ обладают диагностическим и прогностическим по-тенциалом в отношении многих неврологических и психических болезней. В первую очередь это каса-ется шизофрении [46], депрессии [58], эпилепсии [59], болезни Альцгеймера [60], хронического боле-вого синдрома [61], нарушения сознания [62], череп-но-мозговой травмы [63] и др. Проводятся ТМС-ЭЭГ-исследования, направленные на изучение сохранности структурно-функциональной организа-ции мозга при неврологических и психических болез-нях.…”
Section: том 7 Volunclassified